Safety and feasibility of optimized transcranial direct current stimulation in patients with mild cognitive impairment due to Alzheimer’s disease: a multicenter study protocol for a randomized controlled trial - Kim, TaeYeong; Kang, Dong Woo; Salazar Fajardo, Jhosedyn Carolaym; Jang, Hanna; Um, Yoo Hyun; Kim, Sunghwan; Wang, Sheng-Min; Kim, Donghyeon; Lim, Hyun Kook (Frontiers in Neurology, 2024)
Introduction Transcranial direct current stimulation (tDCS) may effectively preserve and improve cognitive function in patients with mild cognitive impairment (MCI). Research has shown that Individual brain characteristics can influence the effects of tDCS. Computer three-dimensional brain modeling based on magnetic resonance imaging (MRI) has been suggested as an alternative for determining the most accurate tDCS electrode position based on the patients’ individual brain characteristics to enhance tDCS effects. Therefore, this study aims to determine the feasibility and safety of applying tDCS treatment using optimized and personalized tDCS electrode positions in patients with Alzheimer’s disease (AD)-induced MCI using computer modeling and compare the results with those of a sham group to improve cognitive function. Method A prospective active-sham group feasibility study was set to recruit 40 participants, who will be randomized into Optimized-tDCS and Sham-tDCS groups. The parameters for tDCS will be 2 mA (disk electrodes R = 1.5 cm) for 30 min during two sets of 15 sessions (2 weeks of resting period in between), using two electrodes in pairs. Using computer modeling, the tDCS electrode positions of each participant will be personalized. Outcome measurements are going to be obtained at three points: baseline, first post-test, and second post-test. The AD assessment scale-cognitive subscale (ADAS-Cog) and the Korean version of Mini-Mental State Examination (K-MMSE), together with other secondary outcomes and safety tests will be used. Discussion For the present study, we hypothesize that compared to a sham group, the optimized personalized tDCS application would be effective in improving the cognitive function of patients with AD-induced MCI and the participants would tolerate the tDCS intervention without any significant adverse effects. Clinical trial registration: https://cris.nih.go.kr, identifier [KCT0008918].